Pengaruh Perhatian Orang Tua Terhadap Hasil Belajar Anak Usia Sekolah Dasar - Sufinatin Aisida (Journal of Creative Student Research, 2025)
Parental attention has a very important role in children's learning outcomes at the elementary school level, the purpose of the study is to find out how much parental attention affects children's learning outcomes at MI Miftahul Jinan. This study uses a quantitative approach with observation data collection techniques, documentation questionnaires and data analysis techniques carried out using simple regression analysis techniques, processed using SPSS 26 for windows software. The normality test used one sample Kolmogrov Smirnov. The linearity test uses Deviation From Linearity. The results of this study show that the significance value is smaller than the probability value of 0.000 < 0.05. It can be concluded that there is a positive and significant influence between parental attention to learning outcomes. The results of the simple regression analysis equation obtained a regression coefficient value of the parental attention variable which is 0.214 where the result is positive so that parental attention has a positive effect on learning outcomes. This means that for every 1 increase in the value of parental attention, the learning outcome score will increase by 0.214. the determination coefficient is 0.350. This means that the influence of parental attention on learning outcomes is 35% while the remaining 65% is influenced by other variables.